The effect of annealing on additive manufactured ULTEM™ 9085 mechanical properties - Zhang, Yongjie (2021)
Fused filament fabrication (FFF) is increasingly adopted for direct manufacturing of end use parts in an aviation industry. However, the application of FFF technique is still restricted to manufacturing low criticality lightly loaded parts, due to poor mechanical performance. To alleviate the mechanical performance issue, thermal annealing process is frequently utilized. However, problems such as distortion issues and the need for jigs and fixtures limit the effectiveness of the thermal annealing process, especially for low volume complex FFF parts. In this research, a novel low temperature thermal annealing is proposed to address the limitations in conventional annealing. A modified orthogonal array design is applied to investigate the performance of ULTEM™ 9085 FFF coupons. Further, the coupons are annealed with specialized support structures, which are co-printed with the coupons during the manufacturing process. Once the annealing process is completed, multiscale characterizations are performed to identify the mechanical properties of the specimens. Geometrical measurement of post annealed specimens indicates an expansion in the layering direction, which indicates relief of thermal stresses. Moreover, annealed coupons show an improvement in tensile strength and reduction in strain concentration. Mesostructure and fracture surface analysis indicate an increase in ductility and enhanced coalescence. This research shows that the proposed annealing methodology can be applied to enhance the mechanical performance of FFF parts without significant distortion.